" The strategy of using Smart Power in U.S Foreign Policy after 2008 (Analytical Study)" - Azhar Abdullah Hassan (Tikrit Journal For Political Science, 2017)
Abstract: The sophistication of international system, the overlap of interests among great states, the change of power balance and the emergence of a number of international and non-international actors at the international arena level may lead the United States, which seeks to maximize its gains, to make a balance between the use of hard and soft power in order to maintain its role and position in the international system .The matter Which has led to the a adoption of the technique of smart power in its foreign policy because it is considered as an integrated strategy that seeks to combine between the hard and soft power, and wise use of pressure when it should be necessary. Particularly nowadays, where the information has become a rapidly spreading and economies have become interrelated ; consequently , the use of smart power has been considered to be a qualitative addition to the USA's power points. This fact particularly can explain to us the secrete behind the great dynamism that American strategy enjoys, which attempts to take the advantages of relatively superiority of the USA in order to achieve its national goals and interests regardless of the damage that may cause to other state as a result of such as a strategy . However, despite the propagation of the notion of smart power, the great impact of the hard power at the international level remains non-changed, especially after the emergence of terrorist organizations such as (ISIS), which should be dealt with by a power and not soft ways, beside the emergence of nuclear powers outside the Western dominance that still rely upon their military power more than any other things instead.